The quasi-Roche lobe overflow state in the evolution of close binary systems containing a radio pulsar - Benvenuto, Omar Gustavo (2015)
We study the evolution of close binary systems formed by a normal (solar composition), intermediate-mass-donor star together with a neutron star. We consider models including irradiation feedback and evaporation. These nonstandard ingredients deeply modify the mass-transfer stages of these binaries. While models that neglect irradiation feedback undergo continuous, long-standing mass-transfer episodes, models including these effects suffer a number of cycles of mass transfer and detachment. During mass transfer, the systems should reveal themselves as low-mass X-ray binaries (LMXBs), whereas when they are detached they behave as binary radio pulsars. We show that at these stages irradiated models are in a Roche lobe overflow (RLOF) state or in a quasi-RLOF state. Quasi-RLOF stars have radii slightly smaller than their Roche lobes. Remarkably, these conditions are attained for an orbital period as well as donor mass values in the range corresponding to a family of binary radio pulsars known as "redbacks." Thus, redback companions should be quasi-RLOF stars. We show that the characteristics of the redback system PSR J1723-2837 are accounted for by these models. In each mass-transfer cycle these systems should switch from LMXB to binary radio pulsar states with a timescale of approximately one million years. However, there is recent and fast growing evidence of systems switching on far shorter, human timescales. This should be related to instabilities in the accretion disk surrounding the neutron star and/or radio ejection, still to be included in the model having the quasi-RLOF state as a general condition.